Estimation of Trade Protection in Middle East and North African Countries - Oliva, Maria-Angels (IMF Working Papers; Working Paper, 2000)
This paper studies the structure and evolution of trade protection in the Middle East and North African (MENA) countries in the 1990s. MENA countries use tariffs and nontariff barriers, and tariff dispersion and nontariff barriers, as substitute protection measures. Tariff levels and tariff dispersion are complements. Excluding Tunisia, the cross-country correlation between tariff and nontariff barriers is -0.46. The correlation between tariff dispersion and nontariff barriers is -0.8. The paper also develops an overall index of trade protection and finds that tariff levels, their dispersion, and nontariff barriers account for 60 percent, 10 percent, and 30 percent of overall protection, respectively.